IMPLEMENTASI TEKNIK BELAJAR POMODORO UNTUK MENINGKATKAN FOKUS BELAJAR PADA MATA PELAJARAN IPS - Roselline Fabelia Valentina; Nugroho Hari Purnomo; Santi Pramanasari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This applied research aims to improve students focus and concentration in learning Social Studies in grade VII-I of SMPN 36 Surabaya by using the Pomodoro Technique. This research was conducted due to the many problems found regarding the lack of focus and concentration in learning among students in grades VII-I. Therefore, the researcher conducted this research using the classroom action research method. The actions in collecting data applied interview, questionnaire, and observation techniques. The research results showed that the percentage of student activity in cycle 1 was 13% in the high category and 15% in the medium category by applying the conventional method, lecturing. On the other hand, in cycle 2 activities, 25% were in the high category and 3% were in the medium category by using the Pomodoro Technique. Thus, it can be concluded that learning using the Pomodoro Technique is effective in helping students improve their focus and concentration in learning Social Studies with the material Understanding Location through Maps in grade VII-I of SMPN 36 Surabaya.